Fashion industry in Kazakhstan: a study in the context of cultural globalization (Journal of Philosophy, Culture and Political Science, 2025)
This article examines the evolution of the fashion industry in Kazakhstan since the period of independence in the context of cultural globalization, analyzing the interaction of traditional cultural heritage and global influences. Through content analysis of fashion media and historical review, the research shows the process of merging and combining Kazakh motifs with modern design. Sustainability and digital platforms are emerging as key drivers of the impact of globalization. The results of the study suggest that while global integration has had an impact on the country’s innovation and economic growth, it also poses obstacles to cultural identity. While globalization has spurred economic growth by fostering innovation and attracting investment, new tensions rose between modernization and cultural preservation. Risks of homogenization and commodification of heritage prompt reflections on identity in a globalized market. By examining these dynamics, the article contributes to broader debates on cultural globalization, offering insights into how post-Soviet nations navigate global integration while reclaiming cultural narratives. Ultimately, Kazakhstan’s fashion landscape emerges as a microcosm of resilience, balancing tradition and modernity in an interconnected world. The study contributes to the debate on cultural globalization, clarifying the direction of global and national development dynamics in post-Soviet Kazakhstan.Key words: Kazakhstani fashion, cultural globalization, fashion industry, traditional attire, sustainable fashion, glocalization